Transcriptome-based analysis of key pathways relating to yield formation stage of foxtail millet under different drought stress conditions - Wang, Jing; Sun, Zexin; Wang, Xinning; Tang, Ying; Li, Xinyi; Ren, Chuanyou; Ren, Jingyao; Wang, Xiaoguang; Jiang, Chunji; Zhong, Chao; Zhao, Shuli; Zhang, He; et al. (Frontiers in Plant Science, 2023)
Although foxtail millet is drought resilient small Panicoid crops, drought stress has significant effect on panicle at yield formation stage. In this study, the changes of panicle morphology, photosynthesis, antioxidant protective enzyme system, ROS system, and osmotic regulatory substance and RNA-seq of functional leaves under light drought stress (LD), heavy drought stress (HD), light drought control (LDCK) and heavy drought control (HDCK) were studied in order to get snap-shot of specific panicle morphological changes, physiological responses and related molecular mechanisms. The results showed that the length and weight of panicle had decreased, but with increased empty abortive rate and then yield dropped off 14.9% and 36.9%, respectively. The photosynthesis of millet was most significantly affected, like net photosynthesis rate, stomatal conductance and transpiration rate were decreased, especially under HD treatment, with reluctant recovery from rehydration. Under LD and HD treatment, the peroxidase (POD) was increased by 34% and 14% while the same as H2O2 by 34.7% and 17.2% compared with LDCK and HDCK. The ability to produce and inhibit O2- free radicals in LD-treated millet leaves was higher than HD. The content of soluble sugar was higher under LD treatment but the proline was higher under HD treatment. Through RNA-seq analysis, there were 2,393 and 3,078 different genes expressed under LD and HD treatment. According to the correlation analysis between WGCNA analysis results and physiological traits, the co-expression network of several modules with high correlation was constructed, and some hub genes of millet in response to drought stress were found. The genes changes relating to carbon fixation, sucrose and starch synthesis, lignin synthesis, gibberellin synthesis and proline synthesis of millet were specifically analyzed. These findings provide a full perspective on how drought effects yield formation of foxtail millet by constructing one work model thereby provide theoretical foundation for hub genes exploration and drought resistance breeding of foxtail millet.